Altered intrinsic regional activity and corresponding brain pathways reflect the symptom severity of functional dyspepsia. Issue 5 (28th January 2014) - Nan, J.; Liu, J.; Zhang, D.; Yang, Y.; Yan, X.; Yin, Q.; Xiong, S.; von, K. M.; Liang, F.; Gong, Q.; Qin, W.; Tian, J.; et al.
Abstract Background Increasing evidence shows central abnormalities in functional dyspepsia (FD) patients, but whether the symptom severity is directly reflected in altered brain patterns remains unclear. The purpose of this study was to explore how FD affected the resting functional brain patterns for different degrees of symptom severity. Methods Functional magnetic resonance imaging was carried out in 40 FD patients and 20 healthy controls. The resting‐state brain changes in regional homogeneity (ReHo) and seed correlation analysis were investigated in patients relative to controls. To what degree the brain changes reflected the severity of the disease was assessed by a pattern classification technique. Key Results Altered ReHo values (p < 0.05, FDR corrected) were discovered in multiple brain areas in FD patients, and only the anterior cingulate cortex (ACC) and thalamus exhibited significant correlation with the severity of dyspepsia symptoms. Compared with controls, the neural signal changes of the thalamus were not found in the less severe FD patient group but in the relatively more severe group, while the ACC showed aberrations in both groups. Seed‐based correlation analysis revealed ACC‐ and thalamus‐related functional connectivity differences between FD patients and controls at a voxel‐wise level, and the altered thalamic circuits provided the best performance in distinguishing FD patients with different levels of symptom severity. Conclusions & Inferences Our results indicated that the functional abnormalities of the ACC and thalamus may occur at different clinical courses in FD. This may help us better understand the progression of FD.